Sleep disturbances and cognitive decline in the Northern Manhattan Study. (4th October 2016) - Ramos, Alberto R.; Gardener, Hannah; Rundek, Tatjana; Elkind, Mitchell S.V.; Boden-Albala, Bernadette; Dong, Chuanhui; Cheung, Ying Kuen; Stern, Yaakov; Sacco, Ralph L.; Wright, Clinton B.
Abstract : Objective: To examine frequent snoring, sleepiness, and sleep duration with baseline and longitudinal performance on neuropsychological (NP) battery. Methods: The analysis consists of 711 participants of the Northern Manhattan Study (NOMAS) with sleep data and NP assessment (age 63 ± 8 years, 62% women, 18% white, 17% black, 67% Hispanic) and 687 with repeat NP testing (at a mean of 6 ± 2 years). The main exposures were snoring, sleepiness, and sleep duration obtained during annual follow-up. Using factor analysis–derived domain-specific Z scores for episodic memory, language, executive function, and processing speed, we constructed multivariable regression models to evaluate sleep symptoms with baseline NP performance and change in performance in each NP domain. Results: In the cross-sectional analysis, adjusting for demographics and the NOMAS vascular risk score, participants with frequent snoring had worse executive function (β = −12; p = 0.04) and processing speed (β = −13; p = 0.02), but no difference in with episodic memory or language. Those with severe daytime sleepiness (β = −26; p = 0.009) had worse executive function, but no changes in the other NP domains. There was no cross-sectional association between sleep duration and NP performance. Frequent snoring (β = −29; p = 0.0007), severe daytime sleepiness (β = −29; p = 0.05), and long sleep duration (β = −29; p = 0.04) predicted decline in executive function, adjusting for demographic characteristics and NOMAS vascular risk score. Sleep symptoms did not explain change in episodic memory, language, or processing speed. Conclusions: In this race-ethnically diverse community-based cohort, sleep symptoms led to worse cognitive performance and predicted decline in executive function.